2006
DOI: 10.1021/bp060081o
|View full text |Cite
|
Sign up to set email alerts
|

In Silico Prediction of Medium Effects on Esterification Equilibrium Using the COSMO-RS Method

Abstract: This paper presents a new approach for predicting solvent effects on esterification reactions of industrial importance in the field of biocatalysis. The COSMO-RS method has been used to calculate the activity coefficients of the chemical species involved in various reactions, carried out in different solvents. For comparison we also used the traditional UNIFAC method. Three lipase-catalyzed esterifications were considered: (1) 1-dodecanoic acid with menthol in n-hexane, n-heptane, cyclohexane, 2,2,4-trimethylp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
24
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 32 publications
0
24
0
Order By: Relevance
“…This method, combining ab initio quantum chemical calculations of solutes and solvents with an effi cient statistical thermodynamics, results in a powerful predictive tool for estimating many thermodynamic properties ( 25 ) . The control of the thermodynamic equilibrium position in biocatalytic processes has been used as a model for evaluating COSMO-RS and comparing it with classical UNIFAC contribution group method ( 4 ) . In this sense, three different lipase-catalyzed esterifi cations were evaluated in different media.…”
Section: Thermodynamics As a Tool To Control Chemical Equilibrium In mentioning
confidence: 99%
See 3 more Smart Citations
“…This method, combining ab initio quantum chemical calculations of solutes and solvents with an effi cient statistical thermodynamics, results in a powerful predictive tool for estimating many thermodynamic properties ( 25 ) . The control of the thermodynamic equilibrium position in biocatalytic processes has been used as a model for evaluating COSMO-RS and comparing it with classical UNIFAC contribution group method ( 4 ) . In this sense, three different lipase-catalyzed esterifi cations were evaluated in different media.…”
Section: Thermodynamics As a Tool To Control Chemical Equilibrium In mentioning
confidence: 99%
“…Actually, thanks to the remarkable properties and useful applications of enzymatic catalysis in nonconventional media, this area of modern biotechnology has turned into a valuable tool for the industrial production of fi ne chemicals ( 4 ) . Among other interesting advantages, the use of nonconventional media in biocatalysis facilitates the solubility of nonpolar substrates and the recovery of products, reduces water-dependent side reactions, and promotes the shift of thermodynamic equilibria favoring the synthesis over the hydrolysis ( 5 ) .…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…As a result COSMO-RS does not depend on experimental data or any parametrization for the solvent so it efficiently enables the calculation of the chemical potential of almost any solute is almost any solvent. Fermeglia et al [22] have evaluated COCMO-RS and UNIFAC in the prediction of solvent effect on the equilibrium position for a series of lipase-catalyzed esterification reactions concluded that COSMO-RS method is very accurate and superior to UNIFAC.…”
Section: Introductionmentioning
confidence: 99%